May Pera sa Gera (There's Money in War) - Covero, Rolando (Social Sciences and Development Review, 2016)
The article presents a different perspective on militarization and wars of aggression waged, historically and currently, by the United States of America against nations and peoples in South and South East Asia, Middle East, Europe, Africa, and Latin and South America. It zeroes in on the enormous money-making dimension of the US-mongered armed confrontations. Also, the paper examines the role the US has played in fanning the flames of war among countries fighting for full-fledged independence and sovereignty. It exposes the real reasons why the US is so into these wars and who really benefits from its arms requirements amounting to billions of dollars.
Keywords: armistice; rogue states; military industrial complex; preemptive strike